PROBLEM OF TYPOLOGIZATION OF THE MODELS OF POWER OF RELATIONS: DOMESTIC REALITIES - Мухамедієв, В. Є. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The author analyzes the models of power relations that have undergone transformational crisis in modern conditions. On the example of Ukraine, the institutional non-compliance with constitutional requirements and the weakness of effective sovereignty are considered. An attempt has been made to change the approach to the problem of inefficiency of the authorities, because it is the immature society that causes the decline of development, and sometimes even a recession. New challenges in modern conditions are the ever-increasing deviation of new-patrimonial regimes in the direction of neo-feudalism.